INTRACRANIAL HEMORRHAGE: EPIDEMIOLOGY, PREVENTION, ETIOLOGY, CLINICAL FEATURES AND PROGNOSIS - N.O. RAKHIMOV¹,²,; KH.D. RAKHMONOV; D.R. SANGINOV; S.SH. BAKHODUROV; M.V. DAVLATOV (Паёми Сино)
The literature review explores various aspects of non-traumatic intracranial hemorrhages (NTIH), including epidemiology, prevention, etiological factors, and clinical features. The search for relevant literature was conducted using databases such as PubMed, Web of Science, Scopus, and eLibrary, covering the period from 2010 to 2023. A total of 1,100 sources were identified, and 68 articles were selected after analysis, reflecting the core topics of interest. The search utilized keywords such as "non-traumatic intracranial hemorrhage", "epidemiology", "prevention", "etiology", "prognostic factors", "outcome", and "clinical signs".